Shear strength improvement of peat soil due to consolidation [compact disc] - 244082 Vivi Anggraini (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2006